Analysis of Technology Acceptance Model on Open Learning Acceptance (Case Study: Universitas Muhammadiyah Pekajangan Pekalongan) - Muhammad Fithrayudi Triatmaja; Panca Kuriniati; T Taufik (Urecol Journal. Part G: Multidisciplinary Research, 2022)
The Covid 19 pandemic has changed the learning process from face-to-face to online, teaching and learning activities at Pekajangan Muhammadiyah University use open learning as a means of online learning. As an evaluation of open learning, it is necessary to carry out user responses to the acceptance of the system that has been used for learning media. This research conducts user acceptance testing (students) of Openlearning at UMPP by using the Technology Acceptance Model (TAM). Data collection for students who are active in the Even Semester 2020/2021 period of Open learning users at Pekajangan Muhammadiyah University which is divided into 3 faculties, namely the Faculty of Health Sciences (Fikes), the Faculty of Economics and Business (FEB), and the Faculty of Engineering and Computer Science ( Fastikom). Obtained questionnaire data that entered a total of 141 respondents. Data analysis using Partial Least Square method with SmartPLS 3.2.9 Software. The results of the study support that Perception of Usefulness and Perception of Ease of Use have a significant effect on Attitude towards Behavior, Perception of Ease of Use has a significant effect on Perception of Usefulness, Perception of Usefulness and Attitude towards Behavior have a significant effect on Behavioral Intentions, and Behavioral Intentions have a significant effect on Real Use System. In general, students using Openlearning at UMPP can accept and use Openlearning as an online learning medium, and greatly assist students in interacting with fellow students during discussions in carrying out lecture assignments.